Visual communication design: a neglected factor in nutrition promotion via packaged food labels - Kelly, Meghan; McCann, Jennifer R.; Chapple, Celeste I.; Woods, Julie; Russell, Catherine G. (Frontiers in Public Health, 2024)
Packaging design is a communication device and a critical component in branding strategy, and has relevance for food policy. Presently, packaging-related nutrition policy initiatives focus on the role of regulated claims, nutrition information panels and front-of-pack nutrition labels to help guide consumer food choices and address high prevalences of discretionary and ultra-processed food consumption in many countries. However, these nutrition labelling systems are not optimized as public health policy tools as many consumers do not use them to inform their food choices. Visual communication design theory posits that a designer orders the elements and principles of design into hierarchies that prioritize certain elements over others, and that some of these elements are more dominant and given more emphasis than others. The overall design of the package thereby directs consumer attention to some aspects of pack design (e.g., characters, contents of the package) and away from others (e.g., nutrition details). Dual processing frameworks propose that food decisions are made with the interplay between automatic and rational thinking processes. Packaging designs affect whether consumers rely predominantly on automatic or rational thinking to select a food. This narrative review outlines the role of food packaging design and how it impacts the clear communication of nutrition aspects of food products and how the use of nutrition information by consumers to make decisions may depend upon design structures in packaging. This article attests that nutrition scientists and policy makers should incorporate visual communication design into research on the food packaging as a public health promotion tool. A stronger focus on the communication of regulated front-of-pack nutrition information can be made with a re-evaluation of the hierarchy of elements in the front-of-pack design enabling consumers to make healthier decisions.